2019
DOI: 10.1080/23802359.2019.1644564
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the hydrothermal vent stalked barnacle Vulcanolepas fijiensis (Cirripedia, Scalpelliforms, Eolepadidae)

Abstract: The family Eolepadidae is the only stalked barnacle in hydrothermal vent regions. Here, we determined the mitogenome of the eolepadid Vulcanolepas fijiensis. The mitogenome was 17,374 bp long, with 76.6% AT content. Its protein-coding gene organization was identical to that of the deep-sea scalpellid Arcoscalpellum epeeum. On the mitogenomic tree, two scalpellomorphan families (Eolepadidae and Scalpellidae) were monophyletic while the other scalpellomorphan family Pollicipedidae did not form the monophyletic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
2
2
0
Order By: Relevance
“…However, the three families under the same order Scalpelliformes were not clustered together, indicating this order is not monophyletic, which is consistent with Lee et al. ( 2019 ). Lepadiformes was located at the base of the phylogenetic tree, the divergence time was earlier than Scalpelliformes, which is similar to the result of nuclear gene analysis (Perez-Losada et al.…”
supporting
confidence: 88%
“…However, the three families under the same order Scalpelliformes were not clustered together, indicating this order is not monophyletic, which is consistent with Lee et al. ( 2019 ). Lepadiformes was located at the base of the phylogenetic tree, the divergence time was earlier than Scalpelliformes, which is similar to the result of nuclear gene analysis (Perez-Losada et al.…”
supporting
confidence: 88%
“…Our mitogenome data indicate that the pollicipedids diverged immediately before the balanomorphs, and were followed closely by the calanticids (Figure 2, Supplementary Figure 1) with robust support. These findings coincide with the Bayesian results of Linse et al (2013), as well as the relatively constant position occupied by the pollicipedids in all mitochondrial genome-based phylogenetic analyses (Song et al, 2017;Cai et al, 2018;Kim et al, 2018;Kim et al, 2019;Chen et al, 2019;Lee et al, 2019;Tian et al, 2020). The mitogenome arrangement of calanticids and pollicipedids more closely resembles the patterns of balanomorphs, except for Smilium sinense which shows remote inversion events of the gene blocks, C-Y-nad1-L1-rrnL-V-rrnS and I-M (Figure 3).…”
Section: Phylogeny and Evolutionary History Of Barnaclessupporting
confidence: 81%
“…our analysis. It had also not been confirmed in the mitochondrial genome analyses of Kim et al (2018); Kim et al, (2019) and Lee et al (2019), or the multiple gene analyses of Linse et al (2013); Rees et al (2014), Herrera et al, (2015, and Kim et al (2022). Furthermore, the mitogenome arrangement of verrucomorph species, which displayed unique gene blocks (Figure 3), was distinctly different from that of the balanomorphs and other barnacles.…”
Section: Phylogeny and Evolutionary History Of Barnaclesmentioning
confidence: 94%
“…Searching on GenBank revealed another mitogenome listed as V. fijiensis (MW291947) linked to the Mao et al (2024) paper, but this too was nested within N. marisindica (Figure 1). Furthermore, a mitogenome of the real V. fijiensis from the North Fiji Basin had already been published (Lee et al, 2019; MN061491) using one of the original specimens sequenced in the description paper, and a BLAST comparison with the mitogenome (MZ772032) presented by Mao et al (2024) revealed a percentage identity of only 88.84% between these two mitogenomes. Altogether, these evidences show that the species identification in Mao et al (2024) was incorrect, and their hydrothermal vent barnacle was actually N. marisindica.…”
Section: Figurementioning
confidence: 99%